Occupation-industry mismatch in the crosssection and the aggregate - Saman Darougheh (Danmarks Nationalbank, 2019)
I define occupations that are employed in more industries as "broader" occupations. I study the implications of broadness for mismatch of the unemployed and vacancies across occupations and industries. I empirically find that workers in broader occupations are better insured against industryspecific shocks. A recent literature has found that mismatch did not significantly contribute to the rise in unemployment during the Great Recession. I build a general equilibrium model that uses occupational broadness as a microfoundation of mismatch. The model uncovers a general equilibrium channel that realigns the strong crosssectional effects of mismatch with its missing aggregate impact. I argue that mismatch across occupations and industries cannot significantly contribute to aggregate unemployment fluctuations.
Keywords: E24; J22; J24; J63; J64; 330; Macroeconomics; labor economics; unemployment; mismatch